The effect of vagal nerve stimulation treatment on autonomic nervous system in patients with refractory epilepsy - Genç, Fatma; Korucuk, Meltem; Uçan Tokuç, Firdevs Ezgi (Frontiers in Neurology, 2025)
IntroductionVagal nerve stimulation (VNS) is a treatment that can be used in drug-resistant epilepsy (DRE) patients who are not suitable for resective surgery. Effects of VNS on the autonomic system are controversial. In our study, we examined SSR and R-R interval variability (RR-IV) to evaluate autonomic functions in patients with refractory epilepsy treated with and without VNS and healthy volunteers.MethodsOur study included 41 healthy volunteers without any disease or drug administration, 38 DRE patients without VNS, and 38 DRE patients with VNS. Electrophysiological tests of sympathetic skin response (SSR) and RR interval variability (RR-IV) analysis were performed.ResultsWhile no statistically significant difference was observed between the SSR latencies and amplitudes of the DRE group with VNS and the DRE group without VNS, when the SSR latencies of the 4 extremities of the DRE groups with and without VNS and the control group were compared, it was observed that both groups had statistically significantly longer SSR latencies in all extremities compared to the control group. A statistically significant difference was observed between the DRE with VNS group and the control group and RR-IV was lower in the DRE with VNS groupConclusionIn conclusion, our study is one of the rare studies investigating the effects of VNS on the sympathetic system in patients with refractory epilepsy. According to the SSR and RR-IV results in our study, there was no evidence that VNS caused sympathetic dysfunction. However, VNS may cause a shift in cardiac sympathovagal balance toward sympathetic dominance.